1979
DOI: 10.1246/bcsj.52.902
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Rate Constants of Reactions of Oxygen Atoms with Several Olefins in Liquid Carbon Dioxide

Abstract: The relative rate constants of reactions of oxygen atoms with several olefins and 2-methylpropane have been determined in liquid carbon dioxide at −18 °C, using the γ-radiolysis of carbon dioxide in the presence of these hydrocarbons. They are : 1-butene, 1.0; cis-2-butene, 2.3; trans-2-butene, 3.0; 2-methylpropene, 2.9; 2,3-dimethyl-2-butene, 2.0; 2-methylpropane, 0.07. These relative values are very different from those obtained in the gas phase. A possible reason is discussed and a simple theoretical treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…cis -4-Octene. To confirm the observations previously reported that cis- or trans 1,2-disubstituted ethylenes yielded, among other products, both cis - and trans -epoxides, in the condensed phase,9i or in the vapor phase, the reaction of cis -4-octene was carried out using an O 2 /He plasma; see Table . The yield of epoxides (99%) formed at moderate (36%) conversion is fully consistent with the proposed mechanism, formation of the triplet diradical adduct, which undergoes internal rotation on a comparable or shorter time scale than intersystem crossing and epoxide formation.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…cis -4-Octene. To confirm the observations previously reported that cis- or trans 1,2-disubstituted ethylenes yielded, among other products, both cis - and trans -epoxides, in the condensed phase,9i or in the vapor phase, the reaction of cis -4-octene was carried out using an O 2 /He plasma; see Table . The yield of epoxides (99%) formed at moderate (36%) conversion is fully consistent with the proposed mechanism, formation of the triplet diradical adduct, which undergoes internal rotation on a comparable or shorter time scale than intersystem crossing and epoxide formation.…”
Section: Resultsmentioning
confidence: 88%
“…When O( 3 P) atoms were generated using a microwave discharge of O 2 /He, the product ratios formed from the oxidation of styrene 9i or cis- stilbene 9a were not appreciably different. However, with all three of the microwave-promoted methods for the generation of O( 3 P) atoms, an appreciable amount of benzaldehyde (5−13%) was formed from the oxidation reactions of styrene 9i. The formation of a cleavage product, benzaldehyde, suggested that under the reaction conditions in all three cases ozone is formed.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations